Pro-Angiogenesis Role of LINC00662 From Esophageal Squamous Cell Carcinoma Cells-Derived Extracellular Vehicles - Li, Feng; Niu, Ren; Gao, ShaoLin; Zhao, FangChao; Dong, Zefang; Zhang, Hao; Li, Shujun (Frontiers in Bioengineering and Biotechnology, 2022)
Objective: LINC00662 is oncogenic in some human cancers, but no much was revealed concerning to its specific action in tumor angiogenesis. Given that, our study investigated the role of LINC00662 from esophageal squamous cell carcinoma (ESCC) cells-derived extracellular vehicles (EVs) in angiogenesis through microRNA (miR)-195-5p/vascular endothelial growth factor A (VEGFA) axis. Methods: Clinical tissue samples were collected from patients with ESCC, in which LINC00662, miR-195-5p and VEGFA expression was analyzed. ESCC cells were transfected, from which EVs were isolated and identified. Human umbilical vein endothelial cells (HUVECs) were co-cultured with the pretreated EVs or transfected with LINC00662 expression vector. After that, viability, colony formation ability, invasion, migration and tube formation ability of HUVECs were observed. Tumor xenograft in nude mice was performed to detect the effect of LINC00662, miR-195-5p or EV specific inhibitor GW4869 on tumor development. Results: LINC00662 and VEGFA were upregulated while miR-195-5p was downregulated in the cancer tissue of patients with ESCC. Silencing LINC00662 reduced viability, colony formation ability, invasion and tube formation ability of HUVECs while overexpressing LINC00662 enhanced these phenotypes of HUVECs. EVs carrying silenced LINC00662 or restored miR-195-5p suppressed angiogenesis in vitro and tumor growth in vivo. VEGFA overexpression reversed miR-195-5p-induced effects on HUVECs in vitro. Conclusion: In summary, inhibited LINC00662 transferred by ESCC cells-derived EVs suppresses angiogenesis through upregulating miR-195-5p and downregulating VEGFA.